2022
DOI: 10.1002/slct.202103545
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Catalytic Reactions for Soot Oxidation on VOx/M (M=KIT‐6, SBA‐15 and SiO2) Catalysts: Influence of Pore Structure

Abstract: In this work, the effect of pore structure for VO x /M (M = KIT-6, SBA-15 and SiO 2 ) catalysts on plasma-catalytic soot oxidation was investigated. The combination of VO x /KIT-6 and plasma shows the highest soot oxidation rate, followed by VO x /SBA-15packed and VO x /SiO 2 -packed plasma reactor. The soot oxidation rate of 97.4 % and the energy efficiency of 0.95 g kWh À 1 can be achieved in plasma-catalytic soot oxidation over VO x /KIT-6 at 30 th min and 20 W. The catalysts were characterized by N 2 adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Ahn et al showed that KIT-6 is a promising catalyst support for LOHC dehydrogenation reactions . The pure-silica mesoporous molecular sieve KIT-6 with an ordered three-dimensional bicontinuous pore structure has the advantages of low acidity, a large specific surface area, and excellent hydrothermal stability. In addition, KIT-6 has abundant surface silicon (Si–OH), which is easy to chemically modify. The application of core–shell/KIT-6 catalysts prepared by a GRR to the H12-NEC dehydrogenation reaction has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ahn et al showed that KIT-6 is a promising catalyst support for LOHC dehydrogenation reactions . The pure-silica mesoporous molecular sieve KIT-6 with an ordered three-dimensional bicontinuous pore structure has the advantages of low acidity, a large specific surface area, and excellent hydrothermal stability. In addition, KIT-6 has abundant surface silicon (Si–OH), which is easy to chemically modify. The application of core–shell/KIT-6 catalysts prepared by a GRR to the H12-NEC dehydrogenation reaction has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial V-based catalysts for SCR reaction also showed great activity in soot oxidation [44,45]. Another application of vanadiumcontaining catalysts in the field of soot combustion is plasma-assisted oxidation [46,47].…”
Section: Introductionmentioning
confidence: 99%